2016
DOI: 10.1111/jeb.12968
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes optimized for early‐life reproduction exhibit faster somatic deterioration with age, revealing a latent cost of high condition

Abstract: High condition enables individuals to express a phenotype with greater reproductive potential. However, life-history theory predicts that reproduction will trade off with somatic maintenance and viability, and several studies have reported faster age-related decline in performance in high-condition individuals, suggesting that high condition in early life is associated with accelerated somatic deterioration. This trade-off may be especially pronounced in males, which often express condition-dependent secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 64 publications
5
18
2
Order By: Relevance
“…Other studies have reported similarly complex phenotypic effects of early life environmental quality: rich larval diets can lead to increased reproductive effort and a shortened lifespan [17,20,21], although we observed the opposite effect here. Given the complex influence of early-life conditions reported in this and other studies, it is not surprising that two recent meta-analyses failed to detect consistent silver spoon effects on lifespan or actuarial senescence in laboratory or wild populations [30,31].…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Other studies have reported similarly complex phenotypic effects of early life environmental quality: rich larval diets can lead to increased reproductive effort and a shortened lifespan [17,20,21], although we observed the opposite effect here. Given the complex influence of early-life conditions reported in this and other studies, it is not surprising that two recent meta-analyses failed to detect consistent silver spoon effects on lifespan or actuarial senescence in laboratory or wild populations [30,31].…”
Section: Discussioncontrasting
confidence: 52%
“…Much of the research on trade-offs between early-and late-life performance has focused on the costs of reproductive investment [15][16][17][18][19]. As future survival is uncertain, individuals with abundant access to resources may allocate highly to early-life performance, leading to more rapid declines with age [17,[20][21][22]. Likewise, but less extensively studied, juvenile growth and development may also influence senescence, and are likely to depend on early-life environmental quality.…”
Section: Introductionmentioning
confidence: 99%
“…If a high‐quality environment during early‐life results in higher rates of early‐life reproduction, then the existence of such trade‐offs leads to a prediction that favorable early environmental conditions should be associated with faster rates of senescent decline in late life. This phenomenon of trade‐offs has recently been demonstrated to occur in lab‐based experiments of arthropods (Adler et al ; Hooper et al ).…”
mentioning
confidence: 74%
“…A meta‐analysis across birds, spiders, insects and fish revealed that the expression of secondary sexual traits is strongly condition‐dependent as the expression of a given sexual trait (known to predict mating success) is generally positively associated with longevity (Jennions, Møller, & Petrie, ). However, while males in good condition during the early stages of life are able to develop the most conspicuous sexual traits, they may suffer from a higher degree of somatic deterioration compared to males that are in low condition during early life, which can lead to an accelerated rate of ageing (Adler, Telford, & Bonduriansky, ). In line with these results, it has recently been argued that the costly nature of secondary sexual traits should be rooted in the theories currently proposed to explain the evolution of ageing (Hooper, Lethonen, Schwanz, & Bonduriansky, ; Tidière et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, while males in good condition during the early stages of life are able to develop the most conspicuous sexual traits, they may suffer from a higher degree of somatic deterioration compared to males that are in low condition during early life, which can lead to an accelerated rate of ageing (Adler, Telford, & Bonduriansky, 2016).…”
Section: Introductionmentioning
confidence: 99%